Branched peptides as bioactive molecules for drug design. Issue 5 (23rd September 2018) - Brunetti, Jlenia; Falciani, Chiara; Bracci, Luisa; Pini, Alessandro
Abstract: Peptides are regarded as good candidates for new biotherapeutics in medicine. Several peptides have already completed clinical development, with more than 60 peptide‐based drugs already on the market, and a further 500 derivatives currently in developmental stages. Branched peptides are an emerging class of synthetic molecules being assessed for drug development. Here, we review possible clinical uses of branched peptides, considering major features such as stability, half‐life, toxicity, and efficacy compared to monomeric peptides, biodistribution, as well as modifications, encapsulation, and conjugation to improve delivery or bypass drug resistance. We focus in particular on the use of branched peptides in oncology and infectious diseases. Abstract :